Effectiveness of cervical spine stabilisation techniques. Issue 4 (27th March 2011) - Boissy, P; Shrier, I; Mellete, J; Fecteau, L; Matheson, G O; Garza, D; Meeuwisse, W H; Segal, E; Boulay, J; Steele, R
Abstract : Background: Proper stabilisation of suspected unstable spine injuries is necessary to prevent (worsen) spinal cord damage. Although the lift-and-slide (L&S) technique has been shown superior to the log-roll (LR) technique to place the body on the spinal board, no studies have yet compared different techniques of manual stabilisation of the c-spine itself. Objective: To compare cervical motions that occur when trained professionals perform the Head Squeeze (HS) and Trap Squeeze (TS) c-spine stabilisation techniques. Design: Cross-over. Setting and participants: 12 experienced therapists. Assessment: HS and TS during lift-and-slide (L&S) and LR placement on spinal board, and agitated patient trying to trying to sit up (AGIT-Sit) or rotate his head (AGIT-Rot). Main outcome measurements: Peak head motion with respect to initial conditions using inertial measurement units attached to the forehead and trunk of the simulated patient. Comparisons between HS and TS with a priori minimal important difference (MID) of 5° for flexion or extension, and 3° for rotation or lateral flexion. Results: Overall, the L&S technique was statistically superior to the LR technique. The only differences to exceed the MID were extension and rotation during LR (HS>TS). In the AGIT-Sit test scenario, differences in motion exceeded MID (HS>TS) for flexion, rotation and lateral flexion. In the AGIT-Rot scenario, differences in motion exceeded MID for rotation only (HS>TS). There was similar inter-trial variability of motion for HS and TS during L&S and LR, but significantly more variability with HS compared to TS in the agitated patient. Conclusion: The L&S is preferable to the LR when possible for minimizing unwanted c-spine motion. There is little overall difference between HS and TS in a cooperative patient. When a patient is confused and trying to move, the HS is much worse than the TS at minimizing c-spine motion.